Body Image Problems and Disordered Eating Behaviors in Italian Adolescents With and Without Type 1 Diabetes: An Examination With a Gender-Specific Body Image Measure - Troncone, Alda; Cascella, Crescenzo; Chianese, Antonietta; Zanfardino, Angela; Piscopo, Alessia; Borriello, Anna; Casaburo, Francesca; del Giudice, Emanuele Miraglia; Iafusco, Dario (Frontiers in Psychology, 2020)
Objective To examine body image problems and their associations with disordered eating behavior in adolescents with type 1 diabetes and well-matched healthy peers. Methods Using a cross-sectional design, 183 adolescents with type 1 diabetes (13.02–18.05 years) were recruited from diabetes centers in southern Italy and compared to healthy peers matched for age and gender. Participants completed self-report measures of disordered eating behaviors (DEPS-r and EDI-3RF) and a gender-specific body image problem questionnaire (SATAQ-4R). Socio-demographic and clinical data (zBMI, HbA1c, and disease duration) were also collected. Hierarchical multiple linear regression analyses were computed to determine the relative importance of diabetes variables and body image problems on participants’ disordered eating behaviors after controlling for demographic variables. Results Adolescents with type 1 diabetes showed diabetes-specific eating problems in 37.7% of cases and had more eating problem symptoms (assessed as drive for thinness and bulimia) than healthy peers. Male adolescents with type 1 diabetes did not display more body image problems (p > 0.05); females with type 1 diabetes compared to females in the control group were found to be more pressured by family (p = 0.025) but less by media (p = 0.022) to improve their appearance and attain a thin body. zBMI and body image problems contributed to a significant increase in disordered eating behavior risk both in male and female adolescents with diabetes and in healthy peers (zBMI 0.213 < β < 0.426, p < 0.05; body image 0.243 < β < 0.572, p < 0.05). None of the variables analyzed were found to significantly predict male bulimic symptoms (all β < 0.296, p > 0.05). Conclusion Since in adolescence type 1 diabetes and insulin therapy may increase the risk of weight gain and promote focus and attention on the body and thus contribute to the development of body image problems and disordered eating behaviors, continuity of medical, nutritional, and psychological care is needed.